Improving the sequence of the technological process of production of Vellur products - Hamdamov Bahrom Raimjonovich; Fattayev Muhammadjon Avazbek o’g’li (Periodica Journal, 2022)
This article is about making changes to the sequence of the Vellur production process and the role of the quality controller. This article describes how to use the quality controller "CIELAB" color detection tester attached to lines 3 and 5.
Keywords: Vellur; quality; production; technological process